Against all odds? Blue economy and blue ocean maritime strategy in Seychelles and Mauritius - Muhammad Ammar Hisham,; Lee, Emma Michelle Yuk Ying Ah-Shung; Kennimrod Sariburaja,; De Garibay, Daniel Ruiz (Penerbit Universiti Kebangsaan Malaysia, 2022)
Does Blue Ocean become the perfect mantra for reaching desired developmental goals? Blue Economy is an important sustainable development framework for coastal and island states who rely on the ocean and marine resources as a source of livelihood. The concept of a Blue Economy merges economic development and conservation for coastal and island states. The Seychelles and Mauritius are two Small Island Developing States (SIDS) in the Western Indian Ocean, faced with economic development and conservation dilemmas. The identification and understanding of the challenges and limitations of Blue Economy for SIDS are required to understand the vulnerability of those nations, which is essential to the future outcomes of sustainable development in the Seychelles and Mauritius. Adopting library research methods and online focus group conversations with different stakeholders in both countries, and over two years, during pre-and post-Covid lockdown periods, provide this paper with fascinating findings. Further identification and understanding of vulnerability, overcoming challenge and paradox of Blue Economic ideals in these two different cases of SDIS refine the authors’ scepticism upon the myth of the SDG. The authors’ preliminary findings explain difficulty of the Covid-19 pandemic in allowing both states to realise their SDG target.